Analisis Tren Penggunaan Instrumen Penilaian Berbasis Digital: Systematic Literature Review (2020-2025) - Tyas, Khusnul Estining Tyas; Lestari, Wahyu; Subali, Bambang; Ellianawati, Ellianawati (Jurnal Dikdas Bantara, 2025)
The advancement of digital technology has brought significant changes in the world of education, including in the implementation of assessments in elementary schools. This study aims to analyze the trend of the use of digital-based assessment instruments at the elementary school level during the period 2020–2025, as well as to identify the challenges and needs for developing innovative and interactive instruments. The method used is a systematic literature review (SLR) by collecting and filtering 1179 articles from Google Scholar and Crossref, with inclusion criteria of only 9 relevant articles. The results of the study showed that the dominance of research was developmental (55.56%), followed by quantitative (22.22%), and no classroom action studies (PTK) were found. The trend shows an increase in the use of digital media such as Quizizz, Wordwall, Google Form, and Kahoot, but there is still a lack of HOTS assessment instruments that are interactive and in accordance with the characteristics of the material, especially in mathematics learning. The main challenges include low innovation in evaluation methods and limited use of digital media. In conclusion, the development of responsive, multimedia, and innovative digital instruments is needed to increase the effectiveness of assessment and student participation, supporting 21st century learning at the elementary level.